Language use in packaging : the reaction of Malay and Chinese consumers in Malaysia - Run, Ernest Cyril De; Chin, Sien Fah (Sunway University College, 2006)
This research sets out to determine the changes in attitude, emotion and behaviour of respondents to packaging using Bahasa Malaysia or Chinese in a multicultural Asian country, Malaysia. The findings of this research indicate that respondents reacted more favorably to product packaging imprinted in their own ethnic language. However, there is no significant difference between respondents in their attitude towards the company, indicating that there is a disparity between consumer reaction towards the company and its product packaging.